Relationship-Based and Arms-Length Financial Systems : A European Perspective - Wolf, Holger (2012)
This paper surveys the debate on arms-length and relationship-based financial systems with a special focus on the Eastern Europe and Central Asia region. The paper argues that while the initial dominance of relationship-based systems in the region is consistent with the implications of the theoretical literature, the subsequent improvements in supporting institutions coupled with structural changes suggests a greater scope for arms-length elements going forward.